ANALISIS KADAR TIMBAL (Pb) PADA SAYURAN SELADA DAN KOL YANG DIJUAL DI PASAR KAMPUNG LALANG MEDAN BERDASARKAN JARAK LOKASI BERDAGANG DENGAN JALAN RAYA TAHUN 2015 - widya eka putri; evi naria; nurmaini * (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Air pollution in Indonesia 70% has caused by motor vehicle emissions that contribute almost 98% of lead into the air. Lead (Pb) is a toxic and dangerous heavy metals that can be toxic to the environment and have an impact on the entire system in the body. Which can be contaminated environment can be air, water, soil, food and others. Vegetables are the example of food that can be contaminated by lead. The objective of this study was to determine the content of lead (Pb) in lettuce and cabbage that sold in Kampung Lalang market Medan based on the distance of trade locations from the highway. The research method is descriptive survey. The examination using Atomic Absorption Spectrophotometer. The study found that the highest lead levels found in lettuce that sold at trade location 0 meter from the highway before washing in the amount of 1.43 mg/kg, once washed lettuce levels of lead decreased to 1.07 mg/kg, and lettuce which closed the levels of lead of 0.69 mg/kg. The highest lead levels in cabbage  that sold at trade location 0 meter from the highway before washing in the amount of 0.57 mg/kg, once washed cabbage levels of lead decreased to 0.39 mg/kg, and cabbage which closed the levels of lead 0.29 mg/kg. The conclusion of this study was the closer the location of trade to the highway, the higher the lead levels found in vegetables. Metal content of lead (Pb) that is checked is still below the threshold limit value requirements established by the Director General of POM Decree No: 03725/B/SK/VII/89 on the maximum limit metal contamination in food that is 2 mg / kg. Traders are advised to pay more attention to the cleanliness of vegetables lettuce and cabbage, for example, provide cover on the vegetables being contaminated by pollutants. To consumers are suggested to wash vegetables before consumed using flowing water.